2012 IEEE International Conference on Power Electronics, Drives and Energy Systems (PEDES) 2012
DOI: 10.1109/pedes.2012.6484321
|View full text |Cite
|
Sign up to set email alerts
|

A signal-based technique for fault detection and isolation of inverter faults in multi-phase drives

Abstract: Abstract-A method for fault detection and isolation is proposed and applied to inverter faults in multi-phase drives. An analysis of simulations in faulty conditions leads to the derivation of suitable fault indices. These are based on the unbalance of the phase currents and their instantaneous frequency. The method is applied to a five-phase permanent-magnet synchronous machine drive. Simulations and experiments validate the proposed method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…As shown in Table 2, SB fault-detection methods have been widely carried out using vector space decomposition (VSD) components [15,18,44,[53][54][55][56][57][58][59][60][61][62][71][72][73][74][75], although monitoring just the phase currents has also been suggested for this purpose [48][49][50][51][52][67][68][69][70], especially in older papers. In a 2012 publication [48], Meinguet et al propose the localization of open-phase faults by quantifying the imbalance of the phase currents, exploiting the fact that these signals are more affected by the occurrence of a fault than the main (α 1 -β 1 ) VSD subspace. The fault is identified after several fundamental cycles.…”
Section: Sb Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 2, SB fault-detection methods have been widely carried out using vector space decomposition (VSD) components [15,18,44,[53][54][55][56][57][58][59][60][61][62][71][72][73][74][75], although monitoring just the phase currents has also been suggested for this purpose [48][49][50][51][52][67][68][69][70], especially in older papers. In a 2012 publication [48], Meinguet et al propose the localization of open-phase faults by quantifying the imbalance of the phase currents, exploiting the fact that these signals are more affected by the occurrence of a fault than the main (α 1 -β 1 ) VSD subspace. The fault is identified after several fundamental cycles.…”
Section: Sb Detection Methodsmentioning
confidence: 99%
“…The main characteristics of the existing detection approaches for phase/switch OC faults in multiphase drives are summarized in Table 2. From this table, it can be observed that some MB [43][44][45][46][63][64][65] and KB [45][46][47]66] solutions for OC identification are available, even though SB ones [15,18,44,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]65,[67][68][69][70][71][72][73][74][75] are the most popular by far.…”
Section: Detection Of Phase/switch Oc Faultsmentioning
confidence: 99%
“…On the one hand, signal-based methods such as current trajectory and instantaneous frequency analysis, considered in refs. [90,91], were applied because of their simplicity and low computational load in detection supervision levels. On the other hand, the model-based techniques were more precise and easier to implement in diagnostic tasks after the mathematical model generation [92].…”
Section: Energy Conversion Stepmentioning
confidence: 99%
“…In the literature, a wide variety of methods used for fault detection can be classified into signal processing approaches [ 18 , 19 , 20 , 21 , 22 , 23 ], model-based approaches [ 23 , 24 , 25 , 26 ], knowledge-based approaches [ 18 , 27 , 28 , 29 ], and data-driven approaches [ 18 , 23 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. With the arrival of technology and the advancement of computing methods, data-driven approaches are gaining attention in the last decades, where it is expected that the data will drive the identification of normal and faulty modes of operation.…”
Section: Introductionmentioning
confidence: 99%